Diclofenac Removal from Wastewater by Iraqi Pillared Clay - Faris Al Ani; Ghayda AL-Kindi; Noor Al-Bidri (Engineering and Technology Journal, 2019)
This study deals with the removal of Pharmaceutical pollutants such as Diclofenac, which caused hazardous pollutant for human health, from aqueous solution. The aim of this study is an investigation to remove the diclofenac from synthesis wastewater by using of pillared clay that made from Iraqi clay (ALAnbar clay) as adsorbent by using both batch and packed bed reactor to study kinetic model. The experimental work in batch reactor using different parameter (diclofenac, pillared clay and pH) in four beakers for 3 hours in jar test instrument , from the result show pH is the important factor effect on the adsorption process and also show diclofenac removal decreased with increasing pH values, but in constant all parameter effect of the initial concentration of diclofenac in the adsorption process show removal of diclofenac increasing with increasing the amount of adsorbent dosage up to 1000 mg. additional, the result of experimental work in packed bed reactor with different variables such as (initial concentration, flow rate and bed depth) for 6 hours, show the best condition of bed depth is 2 cm, initial concentration 625 mg /l and flow rate 25 h/l.